Comparative Evaluation of the Engineering Properties of Asphaltic Concrete from Selected Asphalt Plants in Southwestern Nigeria for Road Construction - Olukayode Olopade, Samson; Adeboje, Adeyemi Oluwaseun; Olutaiwo, Adewale Olukayode; Obisanya, Adekunle Adedapo (International Journal of Sustainable Construction Engineering and Technology, 2023)
In this study, the engineering properties of asphaltic concrete from selected asphalt plants in Southwestern Nigeria for road construction were sampled for three months, analysed and compared with regulatory body specifications. The penetration test, Ductility test, Marshall Stability and flow tests results indicated good conformity to the regulatory specification by all the plants with JBN exhibiting highest range value while LSPWC has the least. Also, asphalt samples from all the plants passed the Ring ball and softening point test with Julius Berger Nigeria having highest value between 53.5-53.7 while SEQUOIA has the least with 50-50.2 when compared to standard value 47-56. For bitumen content tests with 5-8% Specification, ESPRO failed with 3.9-4.8, LSPWC show inconsistence result of 3.9-5.6, SEQUOIA had the highest between 6.4-7.0, while CCECC and JBN conform to specification. The density-void ratio and particle size specification were met by only JBN with major deviation recorded from LSPWC. The result indicated JBN is the only company that satisfy all the engineering properties specification while others exhibit inconsistency in aggregates proportion thereby making the asphalt concrete a possible cause for pavement failure in Southwest Nigeria.